Analysis of Spatial Distribution of Health Care Facilities and its Effects on Access to Primary Healthcare in Rural Communities in Kpandai District, Ghana - John Amoah-Nuamah; Williams Agyemang-Duah; Gmakikube Prosper Ninorb; Borbor Gladstone Ekeme (Taylor & Francis Group, 2023)
AbstractDespite collaborative efforts by the government and the private sector in the provision of health facilities in Ghana, a substantial proportion of communities in rural Ghana still have poor access to primary health care. Employing a case study research design, this study presents an overview of the geographic distribution of healthcare facilities in Kpandai District and access to primary health care. Focus group discussions and interviews were conducted with randomly selected households, opinion leaders, healthcare and in-charges of health facilities to ascertain their perception of accessibility to health services. Geographic Information System (GIS) (ArcMap) was used to model the spatial distribution of health facilities. Spatially, 139 communities representing 50.5% of the communities are not accessible health facilities per World Health Organization and Ghana Health Service Survive distance threshold to health centers and Community-based Health Planning and Services (CHPS), and hospitals, respectively. Ideally, this implies that the majority of the population have to travel for more than 5 km to access health care services. This study found that the poor spatial distribution of health facilities has negative implications on access to primary health care in the district. Poor conditions of roads were a major barrier to the household's accessibility to district hospitals. In addition to this, the availability, affordability, adequacy and acceptability which are major determinants of access to primary health care delivery were found to be fairly good. These findings have implications for the realization of the United Nations' health-related Sustainable Development Goals.